Navigation-guided osteotomies improve margin delineation in tumors involving the sinonasal area: A preclinical study. (December 2019) - Ferrari, Marco; Daly, Michael J.; Douglas, Catriona M.; Chan, Harley H.L.; Qiu, Jimmy; Deganello, Alberto; Taboni, Stefano; Thomas, Carissa M.; Sahovaler, Axel; Jethwa, Ashok R.; Hasan, Wael; Nicolai, Piero; et al.
Highlights: Intratumoral cuts were avoided in all the simulations guided by navigation. Navigation provided a 20% gain in terms of adequacy of margin delineation. Experience, location, and tumor geometry didn't affect the benefit from navigation. Abstract: Objectives: To demonstrate and quantify, in a preclinical setting, the benefit of three-dimensional (3D) navigation guidance for margin delineation during ablative open surgery for advanced sinonasal cancer. Materials and methods: Seven tumor models were created. 3D images were acquired with cone beam computed tomography, and 3D tumor segmentations were contoured. Eight surgeons with variable experience were recruited for the simulation of osteotomies. Three simulations were performed: 1) Unguided, 2) Guided using real-time tool tracking with 3D tumor segmentation (tumor-guided), and 3) Guided by 3D visualization of both the tumor and 1-cm margin segmentations (margin-guided). Analysis of cutting planes was performed and distance from the tumor surface was classified as follows: "intratumoral" when 0 mm or negative, "close" when greater than 0 mm and less than or equal to 5 mm, "adequate" when greater than 5 mm and less than or equal to 15 mm, and "excessive" over 15 mm. The three techniques (unguided, tumor-guided, margin-guided) were statistically compared. Results: The use of 3D navigation for margin delineation significantly improved control of margins: unguided cuts had 18.1% intratumoral cuts compared to 0% intratumoral cuts with 3D navigation (p < 0.0001). Conclusion: This preclinical study has demonstrated the significant benefit of navigation-guided osteotomies for sinonasal tumors. Translation into the clinical setting – with rigorous assessment of oncological outcomes – would be the proposed next step.